Design & development of vehicular micro strip patch antenna for emergency vehicle - Abishek. B, Ebenezer; Arun Raaza, Dr; V. Rajendran, Dr (International Journal of Engineering and Technology, 2018)
Life threat events can occur during Traffic congested peak hours. Emergency vehicles are mostly stuck in the traffic jams because people are unaware of traffic rules, no separate lanes for emergency vehicles. Traffic jams in case of health emergencies and emergencies like fire accident lead to increase in death rate. The loss of precious life can be avoided by efficient traffic management system. In this paper a microstrip antenna is designed and developed with radiation characteristics best suited for the emergency vehicles. Emergency vehicle alert for short-range vehicular networks will be implemented using the fabricated antenna.Â Â